Best distribution and plotting positions of daily maximum flood estimation at Ona River in Ogun-Oshun River Basin, Nigeria (2011)
The paper discusses how Normal, Lognormal, and log-Pearson type 3 distributions were investigated as distributions for modelling at-site annual. maximum flood flows using the Hazen, Weibull, and California plotting positions at Ogun-Oshun river basin in Nigeria. All the probability distributions when matched with Weibull plotting position gave similar values near the center of the distribution but varied considerably in the tails. The Weibull plotting position when matched with Normal, Log-normal and Log Pearson Type III probability distributions gave the highest Coefficient of determinations of 0.967, 0.987, and 0.986 respectively. Hazen plotting position gave minimal errors with the RMSE of 6.988, 6.390, and 6.011 for Normal, Log-normal, and Log-Pearson Type III probability distributions respectively. This implies that, predicting statistically using Hazen plotting position, the central tendency of predicted values to deviate from observed flows will be minimal for the period under consideration. Minimum absolute differences of 2.3516 and 0.5763 at 25- and 50-year return periods' were obtained under the Log-Pearson Type III distribution when matched with Weibull plotting position, while an absolute difference of 0.2338 at 100-year return period was obtained under the Log-Pearson Type 1II distribution when matched with California .plotting position. Comparing the probability distributions, Log-Pearson Type III distribution with the least absolute differences for all the plotting positions is the best distribution among the three for Ona River under Ogun-Osun river basin study location.